2015
DOI: 10.1039/c5ra09039c
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the electron transfer mechanisms for biogas upgrading to biomethane within a mixed culture biocathode

Abstract: a Biogas upgrading is an expanding field dealing with the increase in methane content of the biogas to produce biomethane. Biomethane has a high calorific content and can be used as a vehicle fuel or directly injected into the gas grid. Bioelectrochemical systems (BES) could become an alternative for biogas upgrading, by which the yield of the process in terms of carbon utilisation could be increased.The simulated effluent from a water scrubbing-like unit was used to feed a BES. The BES was operated with the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
47
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(50 citation statements)
references
References 51 publications
2
47
1
Order By: Relevance
“…Particularly, the production of molecular hydrogen (Equation (4)), previous to methane production, was observed to enhance the methane yield through the activity of hydrogenotrophic methanogens found in biocathodes [13]. Such claim was supported by other authors, Batlle-Vilanova et al suggested that only a small amount of methane is directly produced via accepting electrons from the electrode, while most of the production comes from biologically generated hydrogen (Equation (4)) in the biocathode surface followed by hydrogenotrophic methanogenesis [14]. Therefore H 2 is nowadays considered to be the main electron transfer molecule for bioelectrochemical methane production, especially at low applied cathode potentials [15].…”
Section: Introductionmentioning
confidence: 78%
“…Particularly, the production of molecular hydrogen (Equation (4)), previous to methane production, was observed to enhance the methane yield through the activity of hydrogenotrophic methanogens found in biocathodes [13]. Such claim was supported by other authors, Batlle-Vilanova et al suggested that only a small amount of methane is directly produced via accepting electrons from the electrode, while most of the production comes from biologically generated hydrogen (Equation (4)) in the biocathode surface followed by hydrogenotrophic methanogenesis [14]. Therefore H 2 is nowadays considered to be the main electron transfer molecule for bioelectrochemical methane production, especially at low applied cathode potentials [15].…”
Section: Introductionmentioning
confidence: 78%
“…From an economical point of view, however, CO 2 removal is feasible only for biogas produced in large-plants unless novel low cost upgrading approaches are developed. In this context, microbial electrochemical technology has been recently proposed as an innovative and promising tool to upgrade the AD biogas [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, an innovative power-to-gas technology, based on a bioelectrochemical system (BES), was developed for renewable energy surplus storage in the form of biomethane (Figure 1). The term biomethane defines a biogas rich in methane (>95% v/v), obtained from a biological source (like wastewater or sludge), that can be directly used as vehicle fuel or injected into the gas pipeline [2]. The biomethane can be obtained from biogas by different upgrading systems, being water scrubbing the most common one.…”
Section: Introductionmentioning
confidence: 99%
“…These can be obtained in both double-chamber (where anode and cathode are separated by an ionic exchange membrane) or single-chamber BES reactors. The former configuration allows to increase the Coulombic efficiency of the process (ratio of electrons recovered as methane, versus the amount provided as current) but at higher costs due to membrane presence, causing an increase of the internal resistance [2]. The latter configuration, although less efficient, is cheaper to build and operate, and can be easily scaled-up [9].…”
Section: Introductionmentioning
confidence: 99%